The influence of cavitation effects on the purification processes of beet sugar production juices - Mushtruk, Mikhailo; Kos, Tatiana; Vasyliv, Volodymyr; Kryzhova (Vengliyk), Julia; Mukoid, Roman; Bilko, Marina; Kuts, Anatoly; Gunko, Sergiy; Kambulova, Yuliia; Zheplinska, Mariia (My University, 2020)
The existing technology for the purification of diffusion juice and its hardware design has not fundamentally changed over the past four decades. The lack of the necessary theoretical developments and experimental data hinders the development of existing and the development of new technological processes. Therefore, the main direction of improving the purification efficiency of juices of sugar beet production is the disclosure of its unused reserves and their implementation in practice. The scientific problem of choosing the rational direction for improving the technology of juice purification, which ensures the production of consumer granulated sugar in the face of changes in a wide range of quality of raw materials, is relevant and has important economic importance, especially in the context of the transition of beet sugar factories to a market economy. One way to solve it is to make fuller use of the adsorption capacity of calcium carbonate particles while increasing the filtration properties of saturation sediments. Therefore, the study investigates the effect of cavitation effects – vapor condensation and hydrodynamic processing of diffusion juice on the processes of purification of diffusion juice, juices of preliminary defecation, first and second saturations. The analysis of the influence of various effects of cavitation processing of juices from the point of view of improving the purification efficiency, the optimal place of the purification process in the technological scheme of production is established. Існуюча технологія очищення дифузійного соку та її апаратурне оформлення принципово не змінювалися протягом останніх чотирьох десятиліть. Відсутність необхідних теоретичних розробок і експериментальних даних стримує удосконалення існуючих і розробку нових технологічних процесів. Основним напрямом підвищення ефективності очищення соків цукрового виробництва є виявлення невикористаних резервів та їх реалізація на практиці. Наукова проблема полягає у виборі раціонального напряму вдосконалення технології очищення соку, що забезпечує виробництво цукру-піску при змінній якості сировини, що є актуальним та економічно важливим завданням в умовах переходу цукрових заводів до ринкової економіки. Одним із шляхів її вирішення є повніше використання адсорбційної здатності частинок карбонату кальцію при одночасному підвищенні фільтраційних властивостей осаду сатурації. У дослідженні розглянуто вплив кавитаційних ефектів — конденсації пари та гідродинамічної обробки дифузійного соку на процеси очищення дифузійного соку, соків попередньої дефекації, першої та другої сатурації. Проаналізовано вплив різних кавитаційних впливів з точки зору підвищення ефективності очищення, встановлено оптимальне місце обробки у технологічній схемі виробництва.
Keywords: кафедра біотехнології продуктів бродіння і виноробства; кафедра технології хлібопекарських і кондитерських виробів; intensification cavitation; diffuse juice; defecation; saturation; preliminary; кавітація; дифузійний сік; попередня дефекація; сатурація